Epidemiology and key clinical and therapeutic indicators of diabetes mellitus in Russian Federation according to the World Health Organization's strategy goals - I. I. Dedov; M. V. Shestakova; O. K. Vikulova; A. V. Zheleznyakova; M. A. Isakov; D. V. Kutakova; N. G. Mokrysheva (Сахарный диабет, 2025)
BACKGROUND: Diabetes mellitus (DM) is a dangerous challenge to society and high-priority goals for health systems worldwide due to the severity of diabetic complications leading to disability and premature mortality in this category of patients.AIM: To carry out an analysis of epidemiological, clinical and therapeutic characteristics of DM control in the Russian Federation (RF) according to the strategy goals of the World Health Organization (WHO) by 2030 (diagnosis of DM; control of glycemia, blood pressure in DM patients; assignment of statins to DM patients; ensuring the availability of insulin and means for self-monitoring of the level of glycemia) based on the «Database of clinical and epidemiological monitoring of DM in the territory of the Russian Federation (RF)».MATERIALS AND METHODS. The research performed on the basis of the de-personalized "Database of clinical and epidemiological monitoring of DM in the territory of the RF", certificate of state registration database №2020622447 (http://diaregistry.ru, register of DM), which included 87 regions of the RF. Data are presented as cross-sectional study in 01.07.2024.RESULTS: According to the Database of clinical and epidemiological monitoring of DM in the territory of the RF, the target HbA1c<7% is achieved in 29% of patients with type 1 DM (T1DM) and 42% of patients with T2DM. Effective blood pressure control in people with diagnosed DM is achieved in 84% of patients with T1DM and 60% of patients with T2DM. The proportion of patients receiving statins aged 40 and over is 14.1% for T1DM, 15.9% for T2DM. All patients with T1DM (100%) and T2DM on insulin therapy are provided with insulin under the program of state guarantee of drug provision, of them insulin analogues in T1DM — 84,8%, in T2DM — 60,9%, the rest — recombinant human insulins. Self-monitoring devices (glucometers and test strips for them) are provided to 100% of patients with DM. Since 2023, patients with T1DM under 18 years old are provided by continuous glucose monitoring systems.CONCLUSION: Common diabetes monitoring system based on "Database of clinical and epidemiological monitoring of DM in the territory of the RF" at the national level allows to assess the effectiveness of programs to achieve the WHO targets. The data analysis identifies priority areas for the most effective and achievable interventions to strengthen and monitor diabetes control. Providing timely, reliable and sustainable national information on risk factors, epidemiology and clinical data of DM, access to medical drugs and modern technologies of control requires coordinated work by health professionals.